Reinventing Forestry Education to Support Net Zero Emissions 2060 and Indonesia Emas 2045: Integrating Climate Mitigation, Bioenergy, and Human Resource Transformation - Sunarta, Sigit; Permadi, Dwiko Budi; Widiyatno, Widiyatno (Jurnal Ilmu Kehutanan, 2026)
Previous research had shown that climate change often posed a critical challenge to humans, both currently and in the future. This had led to the implementation of targets by countries around the globe for the transition to net-zeroemissions. Indonesia, in particular, had atargetof achieving netzero by 2060, aswell asa national vision of 'Golden Indonesia 2045'. Therefore, this research aimed to discuss the strategic role of the forestry sector in climate mitigation through forest and land management, emissions-reduction actions, carbon-sequestration enhancement, and forest-based renewable energy development. The results emphasized the importance of reinventing forestry education to support the transition. Curriculum transformation toward interdisciplinary, integrative, and collaborative approaches was required to develop adaptive graduate capacities to achieve the targets.